Survival kinetics of Alicyclobacillus acidoterrestris spores in thermally processed pineapple-mango blend juice - Md. Hazmi, N.A.; Mahmud Ab Rashid, N.K.; Abdul Karim Shah, N.N.; Sulaiman, A. (Rynnye Lyan Resources, 2024)
The presence of Alicyclobacillus acidoterrestris (AAT) spores in pineapple and mango juices has been reported in the industry. Thermal resistance of AAT spores to pasteurisation treatment poses a serious threat to the tropical juice industry. This study investigates the influence of formulation (pineapple, mango, 70% mango-30% pineapple and 50% mango-50% pineapple), total soluble solid (10-15°Bx), and pH (3.58-3.70) on AAT (ATCC®49025™) spores’ survivor after processing at 85-95°C. As the temperature rises to 85℃ and 90℃, 1 log reduction of the spores was observed after treatment for 5 mins. Spore concentration for each juice showed a sharp decrease when the temperature reached 95℃, which resulted in a significant reduction (P<0.05) of 3 to 4 log CFU/mL. Significant reductions in pH and total soluble solids of juice samples were noticed in all formulations and D-values of AAT spores heated at 85°C (14.1-16.6 mins) were significantly reduced by double when heated at 90°C (5.8-6.7 mins) (P<0.05). Weibull’s model shows a good fit to AAT spores thermal inactivation behaviour in pineapple-mango juice blends tested in this study with the lowest value of Mean Squared Error (MSE) and Accuracy Factor (Af) close to unity (0.07 ≤ MSE ≤ 0.48; 0.88 ≤ Af ≤ 1.19) compared to first-order model (0.17 ≤ MSE ≤ 3.41; 1.07 ≤ Af ≤ 2.34).